علم الصرف العربي المتقدّم لأغراض علمية (دراسة في الفعل وأبنيته وددلالته وأزمنته من خلال شواهد القرآن الكريم) - Dollah, Nafi@Hanafi (IIUM RESEARCH CENTRE, 2004)

(untitled)
To study about alsorf al-Arabi al-mutaqaddim li-aghradh ilmiyyah min khilal al-Quranul karim theoritically and practically